Mataano Mambio Tradition as Social Capital for Social Balance and Community Welfare among the Laporo People - Dian Puspita Rizki; Suwarti Suwarti (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2026)
This study examines the Mataano Mambio tradition as a form of social capital in maintaining social balance and community welfare among the Laporo community in Kombeli Village, Pasarwajo District, Buton Regency, Indonesia. Although many studies have discussed local wisdom and social capital, limited attention has been given to indigenous harvest traditions as integrated socio-cultural mechanisms that sustain social harmony and collective well-being. This study employed a descriptive qualitative approach. Data were collected through participant observation, semi-structured interviews with 15 informants consisting of traditional leaders, community leaders, youth representatives, and local residents, as well as documentation studies. The data were analyzed using thematic analysis through data condensation, data display, and conclusion drawing/verification. Source and method triangulation were employed to ensure data credibility. The findings reveal that Mataano Mambio strengthens five dimensions of social balance: social solidarity, economic cooperation, cultural preservation, ecological awareness, and spiritual responsibility. Community participation in harvest rituals, customary deliberations, traditional performances, and environmental conservation practices reinforces social cohesion, collective responsibility, and community welfare. The active involvement of younger generations also supports cultural continuity amid modernization and social change. Therefore, Mataano Mambio represents an important form of local wisdom and social capital that strengthens community resilience and promotes harmonious and sustainable social life among the Laporo people.